2019
DOI: 10.1186/s13073-019-0682-2
|View full text |Cite
|
Sign up to set email alerts
|

Low coverage whole genome sequencing enables accurate assessment of common variants and calculation of genome-wide polygenic scores

Abstract: BackgroundInherited susceptibility to common, complex diseases may be caused by rare, pathogenic variants (“monogenic”) or by the cumulative effect of numerous common variants (“polygenic”). Comprehensive genome interpretation should enable assessment for both monogenic and polygenic components of inherited risk. The traditional approach requires two distinct genetic testing technologies—high coverage sequencing of known genes to detect monogenic variants and a genome-wide genotyping array followed by imputati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 35 publications
1
68
0
Order By: Relevance
“…As genome sequencing costs have decreased over the past decade, sequencing-based alternatives to genotyping arrays have been the subject of growing interest (Wetterstrand, 2019). Specifically, low-coverage shotgun whole genome sequencing followed by imputation has been utilized for a number of problems in statistical and population genetics, from providing the backbone for graphbased pangenomes in sorghum to trait mapping in human pharmacogenetics (Tran et al, 2020;Gilly et al, 2019;Rubinacci et al, 2020;Homburger et al, 2019;Wasik et al, 2019;Jensen et al, 2020;Cai et al, 2015a;Liu et al, 2018). As an intuition for why this approach is useful, a sample sequenced at a target coverage of 0.5× is expected to have at least one read on 33 million of the 85 million sites in the 1000 Genomes Phase 3 release, whereas a genotyping array will probe a number of variants which is one to two orders of magnitude fewer, albeit with higher average accuracy (Consortium et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As genome sequencing costs have decreased over the past decade, sequencing-based alternatives to genotyping arrays have been the subject of growing interest (Wetterstrand, 2019). Specifically, low-coverage shotgun whole genome sequencing followed by imputation has been utilized for a number of problems in statistical and population genetics, from providing the backbone for graphbased pangenomes in sorghum to trait mapping in human pharmacogenetics (Tran et al, 2020;Gilly et al, 2019;Rubinacci et al, 2020;Homburger et al, 2019;Wasik et al, 2019;Jensen et al, 2020;Cai et al, 2015a;Liu et al, 2018). As an intuition for why this approach is useful, a sample sequenced at a target coverage of 0.5× is expected to have at least one read on 33 million of the 85 million sites in the 1000 Genomes Phase 3 release, whereas a genotyping array will probe a number of variants which is one to two orders of magnitude fewer, albeit with higher average accuracy (Consortium et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in the literature which investigate the applications of low-pass sequencing often do so by means of simulation or by downsampling (often already-aligned) sequence reads from samples previously sequenced at higher coverages (Gilly et al, 2019;Homburger et al, 2019). While useful, these approaches are unable to capture the real-world idiosyncrasies of data generation in extremely-low coverage sequencing and ignore factors such as the use of different library preparation methods which are optimized for sequencing at given target coverages (Aird et al, 2011;Jones et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One open question is the right moment for consumer genomics to move from array technologies to low coverage sequencing. This manuscript reported that IBD detection can be achieved with 1×LCS and previous work showed that ethnicity estimation (Pasaniuc et al 2012; Li et al 2020; Homburger et al 2019; Rustagi et al 2017) and PRS scores can be calculated with 1×LCS at the same quality of arrays. As such, besides reports based on ultra-rare variants, these lines of study show that 1×LCS covers all main applications in consumer genomics.…”
Section: Discussionmentioning
confidence: 92%
“…Laboratory procedures and imputation for low coverage whole genome sequencing were performed at Color as previously described ( 12 , 13 ). Data from low coverage whole genome sequencing were used to calculate previously published polygenic scores for breast cancer ( 10 ), coronary artery disease ( 9 ) and atrial fibrillation ( 9 ).…”
Section: Methodsmentioning
confidence: 99%